Insider ownership and corporate performance: evidence from Germany - Christoph Kaserer; Benjamin Moldenhauer (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2006)
In this paper we address the question whether insider ownership affects corporate performance. Evidence coming from studies dealing with Anglo-Saxon countries is rather inconclusive, especially because it seems that results are significantly affected by endogeneity. Economically, this is due to the fact that in these countries insider ownership seems to be mainly driven by management's compensation contracts. We argue that Germany is different in this regard, as insider ownership often is related to family control, stock-based compensation is less widespread and the market for corporate control is less developed. Starting from this presumption our data allows to make an unbiased observation as to whether insider ownership affects firm performance. Using a pooled data set of 648 firm observations for the years 2003 and 1998 we find evidence for a positive and significant relationship between corporate performance as measured by stock price performance, market-to-book ratio and return on assets and insider ownership. This relationship seems to be rather robust, even if we account for endogeneity by applying a 2SLS regression approach. Moreover, we also find outside block ownership as well as more concentrated insider ownership to have a positive impact on corporate performance. Overall the results indicate that ownership structure might be an important variable explaining the long term value creation in the corporate sector.
Keywords: 330; Ownership Structure; Shareholder Structure; Insider Ownership; Firm Performance; Corporate Governance; Agency Costs; Lieferanten-Kunden-Beziehung; Industrielle Dienstleistung; Marketingpolitik; Signalling; Kommunikation; Theorie